Harga dan Kualitas Produk sebagai Determinan Minat Beli Produk Preloved di Kalangan Gen Z - Agnestya Sukmawati; Yusita Titi Hapsari; Roro Aditya Novi Wardhani (Universitas Muhammadiyah Surakarta, 2026)
The purpose of this study is to analyze the influence of price and product quality as determinants of interest in buying preloved products among Generation Z in Jember. This research is driven by the rising popularity of preloved fashion as a solution for young people to remain stylish despite economic constraints. Using a quantitative approach, data were collected via structured questionnaires distributed to 130 university students in Jember, selected through purposive sampling techniques. The data analysis included instrument testing (validity and reliability), classic assumption tests, and hypothesis testing using multiple linear regression. The results of the t-test indicate that price (t-count 3.392, sig. 0.001) and product quality (t-count 4.854, sig. 0.000) both have a positive and significant partial effect on purchase interest. Furthermore, the F-test results show a simultaneous significant effect (sig. 0.000) with an R Square value of 0.422, meaning these two variables contribute 42.2% to the purchase interest. This study concludes that a combination of affordable pricing and maintained product functionality drives the shift toward sustainable fashion among Gen Z.